HEGEL'S NEGATIVE THEOLOGY - Lauer, Quentin (Journal of Dharma, 1981)
To those who are even moderately acquainted with Hegel's Science of Logic, which provides the dynamic conceptual fcr the whole of the vast Hegelian " system," it will ccme as r.o surprise that the category of " negativity " assumes for Hegel such. gigantic proportions in the philosophical endeavour. What this Logic seeks to portray throughout its seemingly endless meanderir.gs is the progressive explicitation of the inevitable implications of thought, begi1)X.ing with the very first and inescapable object of thought, namely Being, and ending with the all-embracing logical Idea, which unites the totality of both Thought and Being by at once articulating all the determir-ations of being and giving them meaning in the unity of infinite Being, which is the ultimate condition for the possibility of both thought and being.